2019
DOI: 10.1140/epjc/s10052-019-7007-x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on gluon evolution and geometrical scaling in kinematic constrained unitarized BFKL equation: application to high-precision HERA DIS data

Abstract: We suggest a modified form of a unitarized BFKL equation imposing the so-called kinematic constraint on the gluon evolution in multi-Regge kinematics. The underlying nonlinear effects on the gluon evolution are investigated by solving the unitarized BFKL equation analytically. We obtain an equation of the critical boundary between dilute and dense partonic system, following a new differential geometric approach and sketch a phenomenological insight on geometrical scaling. Later we illustrate the phenomenologic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…The collaborations at HERA contributed high-precision data for measuring the proton structure function F p 2 at different kinematical regions of x and Q 2 [27,28]. Some recent works on the measurement of proton structure functions using various evolution equations and approaches are described in [29][30][31][32][33], and the results correlate well with the experimental data. In [34], for the first time, the reproduction of measurements of the DIS proton structure function at high energy from the color dipole description in momentum space was investigated.…”
Section: Introductionmentioning
confidence: 84%
“…The collaborations at HERA contributed high-precision data for measuring the proton structure function F p 2 at different kinematical regions of x and Q 2 [27,28]. Some recent works on the measurement of proton structure functions using various evolution equations and approaches are described in [29][30][31][32][33], and the results correlate well with the experimental data. In [34], for the first time, the reproduction of measurements of the DIS proton structure function at high energy from the color dipole description in momentum space was investigated.…”
Section: Introductionmentioning
confidence: 84%
“…Some analytical solutions of nonlinear QCD evolution equations incorporating parton-parton recombination can be found in ref. [14][15][16][17]. The parton-parton recombination will tame down the gluon density in the high gluon density region of the scattering process.…”
Section: Introductionmentioning
confidence: 99%
“…In this regime, the dominant parton is the gluon and the key ingredient to calculate the scattering observables is the unintegrated gluon distributions (ugd's) entering through k t factorization formula. The ugd's are characterised by BFKL evolution [7][8][9], which sums the leading a x ln 1 s (…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with our expectation, since BFKL evolution is supposed to be meant for semi-hard probes only, thereby a significant growth can be attributed at large Q 2 . In [9], an extensive study on QCD prediction to the HERA DIS data has been done, but for the modified BFKL equation, which is a nonlinear evolution equation that takes gluon fusion processes into account. However, in that previous work, no significant contribution from gluon shadowing was observed for DIS observables as even the extreme choice of gluon shadowing under study indicated a suppression of only about 10% or less at x=10 −3 for F 2 structure function.…”
mentioning
confidence: 99%